GANGRENOUS GASTRITIS: UNUSUAL CAUSE OF UPPER GI BLEEDING - Iqbal, Umair (Journal of Ayub Medical College Abbottabad, 2019)
Chronic Mesenteric ischemia is an episodic hypoperfusion of small intestine due to atherosclerotic narrowing of mesenteric vessels. Typically, patients report postprandial epigastric pain. The association of abdominal pain with eating results in fear of eating and weight loss. Some patients present atypically with nausea, vomiting and/or GI bleeding likely from gut ischemia. We present here a case of 67-year-old male with history of COPD, Coronary artery disease and atrial fibrillation presented with hematemesis and black stools for one day. Patient reports no abdominal pain or weight loss. He was dizzy and nauseous. He was vitally stable and physical exam including abdominal exam was unremarkable except for the rectal exam which revealed black stools. Investigations revealed Hemoglobin of 16.1 and hematocrit of 45, WBCs of 34000 with 83% neutrophils and bicarbonate of 20. Patient underwent EGD for localizing the site of bleeding and showed stomach lumen completely filled with thrombus which prevented the accurate assessment if gastric mucosa. Repeat EGD was recommended and it revealed gangrenous appearing gastritis throughout with multiple clean ulcers which raised the suspicion of vascular compromise. CT angiography abdomen revealed complete proximal occlusion of Superior Mesenteric artery and near complete occlusion of celiac artery. He underwent successful SMA bypass from left iliac to mid SMA with PTFE graft. Symptoms of mesenteric ischemia can be non-specific and can mimic other etiologies. Clinicians should consider this diagnosis in elderly patient with risk factors of atherosclerosis as early diagnosis reduce complication associated with serious life-threatening disease. Keywords: Gangrenous Gut, Upper GI, Bleeding, Mesenteric Ischemia, Intestinal Angina